Peran Bahasa Indonesia dalam UMKM di Kecamatan Socah - Assabil, Ahmad Zulfan; Saida, Fatma Putri; Sholihah, Siti Lystia Choirotus; Kurniawan, Bima (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic growth through job creation and improving community welfare. In MSME activities, language becomes one of the important factors influencing the effectiveness of communication between business actors and consumers. This study aims to determine the role of Indonesian language in supporting MSME activities in Socah District, Bangkalan Regency, especially in transaction communication, customer service, product promotion, and business development. This research uses a descriptive qualitative method with data collection techniques through interviews and observations of MSME actors in Socah District. The results show that Indonesian language has a strategic function as a communication tool that helps deliver product information clearly, increases customer comfort, and builds a professional business image. Although people in Socah District still frequently use Madurese language in daily interactions, Indonesian is still used as a connecting language when communicating with consumers from outside the region. The proper use of Indonesian helps MSME actors reduce misunderstandings, improve service quality, and expand marketing opportunities. However, several obstacles were found, such as the dominance of local language and the limited ability of some business actors to use Indonesian effectively in promotional activities. Therefore, improving language literacy through business communication training is needed so that MSMEs can develop and compete in a wider market. This study emphasizes that Indonesian language is not only a communication medium but also an important factor in supporting MSME sustainability and competitiveness.